Improved preoperative clinical staging system for intrahepatic cholangiocarcinoma using the ABC factors: a retrospective study - Huang, Yiyun; Ye, Wenkai; Huang, Junnan; Xu, Linwei; Zhang, Yuhua; Xing, Renwei; Zhang, Zewei (Frontiers in Oncology, 2026)
ObjectiveThis study aimed to assess the prognostic significance of ABC factors, including anatomical factors (A), biological factors (B: carbohydrate antigen 19–9 [CA19-9]), and patient condition (C) or performance status (PS), in intrahepatic cholangiocarcinoma (ICC) patients who underwent surgery, with the ultimate goal of enhancing the preoperative clinical staging system for the diagnosis of ICC.MethodsWe retrospectively analyzed the clinical data of 217 patients who underwent radical surgery for intrahepatic cholangiocarcinoma at the Zhejiang Cancer Hospital between January 2010 and August 2022. All patients were stratified into early (EA), intermediate (IM), and locally advanced (LA) stages, according to radiological findings. Multivariate Cox proportional hazards analysis was used to examine the impact of ABC factors on overall survival (OS) and disease-free survival (DFS).ResultsOverall, 107 (49.3%), 86 (39.6%), and 24 (11.1%) patients were diagnosed with EA, IM, and LA, respectively. The preoperative CA19–9 level in 73 patients (33.6%) was >500 U/mL. The performance status score of 53 patients (24.4%) was ≥1. The independent risk factors for OS and DFS were IM, LA, CA19-9 >500 U/mL and performance status score ≥1. The median OS was 32.2, 20.4, 11.0, 9.8, and 6.8 months and the median DFS was 19.3, 14.8, 7.7, 5.9, and 3.3 months for patients with ABC composite scores of 0 to 4.ConclusionABC is an independent prognostic factor for OS and DFS in patients undergoing radical surgery for ICC. The preoperative clinical staging of patients with ICC should fully consider the anatomical, biological, and PS factors.